The Effect of Good Corporate Governance (GCG) on Financial Performance with Corporate Social Responsibility (CSR) as an Intervening Variable (Empirical Study on Primary Consumer Sub Sector Companies Listed on The IDX 2018 - 2022) - Amalia Rusda; Rijal Suryarahmadtullah (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Bogor, 2024)
This research aims to examine the influence of Good Corporate Governance (GCG) including institutional ownership and the board of commissioners on financial performance with Corporate Social Responsibility (CSR) as an intervening variable. This research uses financial performance as the dependent variable and Good Corporate Governance as a proxy for institutional ownership and the board of commissioners as the independent variable and Corporate Social Responsibility (CSR) as the intervening variable. This type of research is associative research. This research uses secondary data in the form of annual financial reports originating from the Indonesia Stock Exchange (BEI). The population in this research is Primary Consumer Sub-Sector Companies listed on the Indonesia Stock Exchange 2018-2022. The sampling technique in this research used a purposive sampling method, 7 companies were obtained as research samples. The data analysis technique in this study uses the multiple linear regression analysis method and the data analysis tool in this study uses the Eviews version 12 software program. The results of the study show that GCG and CSR together have a positive effect on the company's financial performance, while the proxies for institutional ownership and the board commissioner is partially insignificant. Likewise, CSR does not have a significant impact on financial performance. In addition, the board of commissioners proxy influences financial performance through CSR as a moderation, while the institutional ownership proxy does not have a similar effect.Keywords: Good Corporate Governance, Institutional Ownership, Board of Commissioners, Corporate Social Responsibility, Financial Performance